2019
DOI: 10.1177/1071100718818572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Syndesmotic Implant Removal on Dorsiflexion

Abstract: Background: There is limited evidence that syndesmotic implant removal (SIR) is beneficial. However, many surgeons advocate removal based on studies suggesting improved motion. Methodologic difficulties make the validity and applicability of previous works questionable. The purpose of this study was to examine the effect of ankle dorsiflexion after SIR using radiographically measured motion before and after screw removal utilizing a standardized load. Methods: All patients undergoing isolated SIR were candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Clinical outcomes, like range of motion, were reported in six studies. (23,24,30,(33)(34)(35) For the cohort studies and one before-after study, there was no difference in the outcomes, (23,24,35) while the other three before-after studies showed advanced range of motion. (30,33,34) Garner et al measured two components of the Short Form 36 scale for quality of life, with better outcomes for physical components in the removal group.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 91%
See 4 more Smart Citations
“…Clinical outcomes, like range of motion, were reported in six studies. (23,24,30,(33)(34)(35) For the cohort studies and one before-after study, there was no difference in the outcomes, (23,24,35) while the other three before-after studies showed advanced range of motion. (30,33,34) Garner et al measured two components of the Short Form 36 scale for quality of life, with better outcomes for physical components in the removal group.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 91%
“…The literature search identi ed 13 eligible studies.) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) The studies were conducted in Germany, (26)(27)(28) the USA, (29,30,32,33) Switzerland, (22,34) Singapore, (23) New Zealand,(24) the UK, (31) and Japan. (35) Moreover we identi ed a protocol on an ongoing RCT regarding syndesmotic screw removal conducted in the Netherlands (36) and an entry on clinicaltrials.gov about an RCT regarding removal/retaining material in Lisfranc fractures conducted in Canada.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations